2016
DOI: 10.1038/srep35963
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D1 regulates focal adhesion dynamics and cell adhesion through Phosphatidylinositol-4-phosphate 5-kinase type-l γ

Abstract: Focal adhesions (FAs) are highly dynamic structures that are assembled and disassembled on a continuous basis. The balance between the two processes mediates various aspects of cell behavior, ranging from cell adhesion and spreading to directed cell migration. The turnover of FAs is regulated at multiple levels and involves a variety of signaling molecules and adaptor proteins. In the present study, we show that in response to integrin engagement, a subcellular pool of Protein Kinase D1 (PKD1) localizes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 81 publications
(97 reference statements)
1
14
0
1
Order By: Relevance
“…Now that we have identified RhoA-Src-pY87-PKD2 signaling as a mechanism to target PKD2 to the FAs, prospective targets for PKD2 in this pathway still need to be identified in future studies. Possible substrates for PKD2 at the FAs could include FA-localized phosphatidylinositol-4-phosphate 5-kinase type-l γ (PIP5Klγ), which previously has been shown to be a target for PKD1 37 , and depletion of PIP5Klγ leads to severe attachment and cytoskeletal defects in cells 38 . PIP5Klγ regulates PI4,5P 2 levels, and such alterations regulate proper FA function and FA dynamics 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Now that we have identified RhoA-Src-pY87-PKD2 signaling as a mechanism to target PKD2 to the FAs, prospective targets for PKD2 in this pathway still need to be identified in future studies. Possible substrates for PKD2 at the FAs could include FA-localized phosphatidylinositol-4-phosphate 5-kinase type-l γ (PIP5Klγ), which previously has been shown to be a target for PKD1 37 , and depletion of PIP5Klγ leads to severe attachment and cytoskeletal defects in cells 38 . PIP5Klγ regulates PI4,5P 2 levels, and such alterations regulate proper FA function and FA dynamics 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously have shown that PIP5K1C lipid kinase activity is inhibited after phosphorylation at serine 448, and have generated a phospho-specific antibody (pS448-PIP5K1C) for this site [ 9 ]. Therefore, we investigated if the phosphorylation status of PIP5K1C at S448 is altered with increasing invasiveness of breast cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Altered FA dynamics due to decrease in PIP5K1C activity or expression has been linked to increased cell migration and invasion [ 6 , 7 ]. PIP5K1C localization to FA is negatively-regulated by p35/Cdk5-mediated phosphorylation at S650 [ 8 ]; and PIP5K1C degradation is regulated by phosphorylation through p70S6K1 at threonine 553 and serine 555 [ 7 ], while its lipid kinase activity is inhibited after phosphorylation through protein kinase D (PKD) at serine 448 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, as curvas de sobrevida construídas no KM Plotter demonstram a alta expressão do gene parece ter impacto positivo na sobrevida das pacientes, podendo atuar como um marcador de prognóstico. Uma das explicações possíveis para esta relação seria o fato de que PRKD1 participa da manutenção das características epiteliais dos tecidos em que é expresso, evitando o início do processo de metástase, através de: 1) estabilização da adesão focal entre as células e a matriz celular ao fosforilar a enzima PIP5Klγ (fosfatidilinositol-4-fosfato 5-quinase tipo-l gama) na Ser 448 próxima ao domínio quinase, levando a diminuição da sua capacidade de fosforilar PI4,5P2 (fosfatidilinositol 4,5bisfosfato) e impedindo o turnover da adesão focal (Durand et al, 2016) e 2) inibição da capacidade de migração das células, através da fosforilação de SSH1L na Ser 978 , o que facilita a ligação da proteína 14-3-3, causando diminuição da capacidade de SSH1L de desfosforilar e ativar cofilin, responsável por romper e despolimerizar os filamentos de actina para criação de novos filamentos e, consequentemente, da formação da protusões celulares (Eiseler et al, 2009b).…”
unclassified